“Strata of conscious peasant intelligentsia”: the cooperative movement of the first decades of the 20th century – the sphere of social mobility of the Ukrainian peasantry and the formation of a new sociocultural type of intelligentsia - Fareniy, Igor (Ukrainian Peasant, 2025)
The purpose of the article is to show the formation of an intellectual stratum of representatives of the peasantry in the cooperative movement of the first decades of the 20th century and the nature of its social culture. Scientific novelty. The cooperative movement is shown as a sphere in which representatives of the peasantry acquired the social status of the intelligentsia with specific cultural features. Conclusions. The cooperative movement of the first decades of the 20th century was a sphere in which the cooperative peasantry mastered organizational and managerial activities, new achievements in education and culture, and acquired the social status of the intelligentsia. The cooperative movement objectively created conditions for the formation of the necessary professional personnel from among representatives of the peasantry, capable of working in cooperative organizations. Peasant cooperatives promoted peasants who were capable of organizational work and socially responsible to leadership positions. Cooperative organizations, public organizations, and self-government bodies created courses and educational institutions to train specialists for cooperation, which also contributed to the growth of the general educational and cultural level of the students. The social composition of the cooperative, the elective principles of forming its governing bodies, and the system of cooperative education created conditions for representatives of the cooperative peasantry to acquire the social status of the intelligentsia. Formed from representatives of the peasantry, the intelligentsia had specific characteristics: it possessed skills in public, cooperative, and managerial activities, saw its social mission in serving the people, and was dependent on them. Contemporaries identified it as a specific cultural type of intelligentsia, as an independent social class – the peasant intelligentsia. The emergence of the peasant intelligentsia was objectively caused by the existence of cooperation as an economic system, which led to changes in the social structure of society.